Hubungan Kekhawatiran Wisatawan Keluarga terhadap Pelaksanaan Parenting Health Education pada Masa Pandemi Covid-19 di Kids Club Hotel Nusa Dua - Ni Made Dewi Ayu Virgayanti; I Nyoman Ribek; Ni Luh Putu Yunianti Suntari Cakera (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2022)
In Indonesia, family celebrations fall ill with 36% of children getting sick while traveling. The purpose of this study was to determine the relationship of family tourists to the implementation of parenting health education during the Covid-19 pandemic at the Kids Club Hotel Nusa Dua in 2022. This research was conducted in March-April 2022 using the correlation method with the approach used, namely cross-sectional. The sample used was 106 family tourists who brought their children to visit the Kids Club Hotel Nusa Dua using the Purposive Sampling technique. Statistical testing using Spearman rank correlation test. The characteristics of the elderly respondents obtained were the average age of respondents from family tourists 26-35 years, 58% with the most gender being 70.8% female. characteristics of visitors aged 6 years 36% with male gender 60%. Activities carried out when children visit the Kids Club as much as 50% carry out the main activity, namely playing games that have been prepared at the Kids Club. Holiday levels. Family tourists' concerns about the implementation of parenting health education have a significant relationship with the p value = 0.001 (0.05). So it is necessary to provide counseling to tourists so that they can control so that anxiety disorders do not occur so that they carry out parental health education to the maximum.